Sentiment Analysis of TikTok Application on Twitter using The Naïve Bayes Classifier Algorithm - Denia Putri Fajrina; Syafriandi Syafriandi; Nonong Amalita; Admi Salma (Departemen Statistika Universitas Negeri Padang, 2023)
TikTok is a popular social media platform that has gained a lot of attention lately. People of all ages are using this application to share short videos with their friends and followers. The content on TikTok is diverse and can be tailored to individual preferences, but there have been concerns about the presence of vulgar content that can be viewed by minors as there are no age restrictions. This has led to public scrutiny of the application on social media platforms like Twitter. To address this issue, sentiment analysis was conducted on reviews of the TikTok application to help users make informed decisions about its use. The aim of this analysis was to determine whether people's opinions about TikTok were positive or negative. To achieve this goal, researchers used the hashtag